Find the Bug A Book of Incorrect Programs - Barr, Adam (Addison-Wesley Professional, 2004)
50 exercises to help you find bugs faster -- with less aggravation! Bug hunting is an art, and you need to be a master . Get Find the Bug, and you'll become one. Long-time Microsoft programmer Adam Barr presents 50 programs, each with exactly one bug. Your assignment: find it. As you do, Barr will teach you how to "think like your processor" ... anticipating exactly how code will behave, even without running it. You'll learn better ways to read code, understand it -- and above all, improve it. Whether you're building new systems or maintaining someone else's, you'll find bugs earlier, faster, with less frustration ... and write cleaner code to begin with. Presents "bugged" programs in C, Java, Python, Perl, and x86 assembly language, with carefully explained solutions Includes language overviews to help you debug all 50 examples, even if you don't know the language Shows how to look past the "surface" of code to uncover its hidden internal logic Offers practical guidance on analyzing programs, including specific inputs to test Presents a wide range of realistic bugs, with no phony "gotchas" Draws on the types of coding and debugging challenges Microsoft uses to interview new programmers An indispensable resource for working programmers, maintainers, testers, quality specialists, and everyone involved in code reviews © Copyright Pearson Education. All rights reserved.